2019
DOI: 10.1002/jcp.28130
|View full text |Cite|
|
Sign up to set email alerts
|

Restoration of microRNA‐30b expression alleviates vascular calcification through the mTOR signaling pathway and autophagy

Abstract: Pathological calcification represents an event that consequently leads to a distinct elevation in the morbidity and mortality of patients with chronic kidney disease (CKD) in addition to strengthening its correlation with hyperphosphatemia. Epigenomic regulation by specific microRNAs (miRNAs) is reported to be involved in ectopic calcification. However, the finer molecular mechanisms governing this event remain unclear. Hence, this study aimed to identify the potential miRNAs involved in vascular calcification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Meanwhile, 62 rats successfully underwent VC development, and success rate was calculated to be 87.10% (54/62). Based on the standard two-step surgical ablation procedure, CKD was induced by 5/6 nephrectomy (5/6 Nx; Xu et al, 2019). The left kidney was simply removed by two-thirds.…”
Section: Ethics Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, 62 rats successfully underwent VC development, and success rate was calculated to be 87.10% (54/62). Based on the standard two-step surgical ablation procedure, CKD was induced by 5/6 nephrectomy (5/6 Nx; Xu et al, 2019). The left kidney was simply removed by two-thirds.…”
Section: Ethics Statementmentioning
confidence: 99%
“…Upon reaching 80-90% confluence, cells were detached in 0.25% trypsin (25200056, Gibco), followed by passaging. VC cell models were induced with 10 mmol/L β-glycerol phosphate (50020, Sigma-Aldrich, St Louis, MO, United States) for 9 days, whereas the control group was treated with equal volumes of phosphate buffer saline (PBS; Xu et al, 2019). β-glycerol phosphate-induced VSMCs were transduced with shRNAs targeting OGT, NRF2, or KEAP1, overexpression plasmids of OGT (oe-OGT), alone or in combination, as well as their controls.…”
Section: In Vitro Model Of Vsmc Calcificationmentioning
confidence: 99%
“…For example, the miR-30 family has been reported to inhibit vascular calcification. 19 , 20 , 21 , 22 , 23 miR-125b 24 and miR-135a 24 are also anti-calcification miRNAs. In contrast, miR-32 , 24 miR-324-3p , 25 and miR-486 26 are examples of pro-calcification miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 15 (40.5%) have been confirmed or are suspected to promote or aggravate VC in different scenarios, while 22 (59.5%) protect against VC formation or progression. Direct gene targets have been identified for 14 miRNAs with negative VC regulatory capacity, including miR-29a/29b [14], miR-29b-3p [34], miR-30b [16,47], miR-30c [16], miR-30e [25], miR-34b/34c [29,64], miR-125b [13,22] miR-133a [19], miR-135a [30], miR-182 [42], miR-204 [15,41,50], and miR-205 [21], while few direct targets have been identified for miRNAs with VC enhancement ability (miR-34a [39], miR-128-3p [48], and miR-135a-3p [17]). In the following sections, we describe the clinical features of each VC-regulating miRNA based on their propensity for positive or negative vascular influences.…”
Section: Mirnas In Vc: Positive and Negative Vc Regulatorsmentioning
confidence: 99%
“…Louvet et al also reported that miR-30b was down-regulated during in vitro human VSMC calcification [28]. Other researchers used mouse or rat VSMC and tissues for analysis; they showed similarly that miR-30b and miR-30e over-expression alleviated VC, but the direct targets in murine VSMCs (insulin-like growth factor 2 [IGF2] and SOX9) seemed to differ from those (RUNX2 and Smad1) of human ones, and the mechanisms involved varied as well (mTOR pathway in murine cells) [25,47].…”
Section: Negative Vc-regulating Mirnasmentioning
confidence: 99%